Grewia gum as a potential aqueous film coating agent. I: Some physicochemical characteristics of fractions of grewia gum - Ikoni J Ogaji; Ignatius S Okafor; Stephen W Hoag (Wolters Kluwer Medknow Publications, 2013)
Background: Grewia gum has received attention as a polymeric pharmaceutical excipient in the recent times, being employed as a suspending, film coating, mucoadhesive, and binding agent. The low aqueous solubility, however, has limited its characterization and application. Objective: The purpose of this study was to fractionate and evaluate some physicochemical properties of the gum. Materials and Methods: Aqueous dispersion of the gum was treated at 80΀C for 30 min in the presence of sodium chloride and was subsequently fractionated by successively centrifuging it at 3445 rpm for 30 min. Skeletal density, solubility, particle size, and rheological as well as thermal characteristics of the fractions were evaluated. The 1 H nuclear magnetic resonance (NMR) and near infrared (NIR) profiles of the fractions were also investigated. The solubility of the gum increased up to fourfold while the viscosity decreased from 244 to as low as70 cP at 40 rpm with some fractions. Results: Grewia gum and the fractions showed good thermal stability exhibiting no thermal events, but charred irreversibly at 297΀C irrespective of the fraction. The molecular weight averages by weight and by number of the fractions were between 233,100 and 235,000. The 1 H nuclear magnetic resonance (NMR) spectra showed broad peaks. The NMR and NIR spectra suggested the presence of -OH and -OCH 3 functional groups in this gum. Conclusion: The fractionation improved solubility and facilitated further investigations on its characteristics that may have implication on its processing, application, and optimization as a potential pharmaceutical excipient.